POLRI SEBAGAI GARDA TERDEPAN DALAM PENEGAKAN HUKUM KORUPSI DIGITAL DI ERA TRANSFORMASI TEKNOLOGI - Afriansyah, Donal; Torrido, Aryan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2024)
Law continues to develop along with advances in information technology, influencing communication patterns and various aspects of people's lives. Although technology offers many solutions, it also presents challenges, especially in eradicating corruption, which increasingly involves digital data. Cyber ​​security is very important in protecting data, especially those related to corruption crimes. In the digital era, corruption crimes are increasingly difficult to detect and uncover because perpetrators often use technology to evade law enforcement. Therefore, an effective approach is needed to ensure that perpetrators are arrested and prosecuted in accordance with applicable law. This research aims to analyze human resource management in the police environment as a strategy to overcome these challenges by improving human resource performance through a qualitative approach, where this type of research emphasizes processes and meanings that are not tested or measured precisely. This research uses a method where the materials studied in normative legal research are library materials or secondary data. Library materials consist of primary sources and secondary sources. Primary sources include: literature books, research reports, magazines, theses, dissertations, and patents. Meanwhile, secondary sources include: abstracts, indexes, bibliographies, government publications and other reference materials. with data in the form of descriptive data. To mitigate the negative impacts of digital technology, adequate awareness and understanding of the wise and safe use of technology is very important. Education and increasing awareness regarding the risks of digital technology is very important, both for individuals and society as a whole. The National Police of the Republic of Indonesia (Polri) has a major responsibility in enforcing the law against technology-related crimes, such as cybercrime, online fraud, dissemination of illegal content, and copyright violations. By strengthening existing regulations and increasing the capacity of the National Police in investigating and taking action Digital crime is expected to reduce corruption cases that utilize information and communication technology. Digital corruption is a big challenge in this digital era, which requires continuous efforts to deal with it.